USING THE MPS-PA AS A QUANTITATIVE TOOL TO PRODUCTION INDICATOR FORMULATIONS - Augusti, Natália Carolina; Mendes, Oswaldo Lázaro (Revista Interface Tecnológica, 2022)
The current scenario has generated several changes in all sectors of the economy, increasing competitiveness and the need for improvement in processes. Simulation seeks to optimize processes, reducing losses and improving processes, as errors are corrected in tests. The present work aims to simulate production processes and perform a quantitative comparison of the means of production control. As a basis for this project, bibliographic research based on books, internet articles and on-site visits were used to collect data. The work used the methodologies of Brainstorming and Design Thinking and through the use of MPS-PA compact workstation from FESTO simulated production processes (manual process, semi-automatic process and automatic process) of pasteurization. As a result, the simulation showed an improvement in the semi-automatic process in relation to the manual one, but the advantage of the automatic process in relation to the other two, manual and semi-automatic, is expressive. It is concluded that the use of simulation in production makes it possible to visualize the scenarios and their possible results without impacting the production process.